Characterization of the Antioxidant Properties of Seeds and Skins in Selected Turkish Grapes - OZTURK UREK, RAZIYE; AYAR KAYALI, HULYA; TARHAN, LEMAN (Asian Journal of Chemistry, 2010)
1,1-Diphenyl-2-picryl-hydrazyl (DPPH•), hydroxyl (HO•), superoxide anion (O2•−) radicals scavenging activities and total antioxidant capacities; total phenolic, catechin and epicatechin contents were determined in ethyl acetate-water extract (EAWE) and methanol-water extract (MWE) extracts of selected six varieties of Vitis vinifera L. from Turkey grape seeds and skins. DPPH• scavenging capacities of 95 % were determined for 0.14 μg/mL of seed and 2.01 μg/mL of skin EAWEs of Eksi kara grape. O2•− scavenging capacities were observed only in EAWEs of all grape seeds. The highest HO• scavenging capacity was also reached to 98 % with 0.5 μg/ mL of EAWE of Eksi kara grape seed. Total antioxidant capacities of seed extracts were generally higher than skin extracts. Total phenolic contents in seed EAWEs were ranged from 5.34 to 101.7 μg gallic acid/μg extract. Catechin and epicatechin levels in seeds and skins were higher in EAWEs by comparison with MWEs. The radical scavenging capacities of Eksi kara grape seed and skin extracts, which had the highest values,were decreased between 10-20 % after heating process although the increases of their total phenolic contents.